A quick review of infrared thermography studies on children and adolescents’ mental health - Zhao, Jing; Hong, Xu; Zhang, Xinran; Li, Ying; Ma, Yiming; Zhang, Ziying; Huo, Siyu; Sun, Yudi (Frontiers in Psychiatry, 2025)
IntroductionInfrared Thermography (IRT) is valuable for monitoring surface temperature distributions, with proven benefits in assessing physiological states. However, most research focuses on adults, neglecting its potential for evaluating children and adolescents, whose mental health significantly impacts learning and social adaptation. This study aims to review the applications of IRT in different psychological health fields and identify gaps in its clinical diagnostic standards for pediatric psychological assessment.MethodsA rapid review approach is employed to search for literature on the applications of IRT in emotional disorders, Autistic Spectrum Disorder (ASD), Post traumatic stress disorder (PTSD), stress, and cognitive load from PubMed, ScienceDirect, Google Scholar and PLOS ONE. The included articles were subjected to manual screening and qualitative analysis. After screening 2395 citations and excluding low-quality ones, 27 out of 50 reviewed articles were included.ResultsFor children, IRT can capture facial temperature changes caused by autonomic nervous system responses to emotional disorders. In ASD, IRT can detect temperature changes related to emotional and cognitive states, enhancing diagnosis and insights into sensory processing and emotional regulation. Additionally, IRT can capture the emotional, stress, and psychological responses of PTSD patients. For cognitive load, relying solely on self-reporting frequently lacks objectivity, while IRT offers a non-invasive, real-time method across various scenarios.DiscussionIRT has revealed correlations between physiological reactions and changes in body temperature detectable by thermal imaging, leading to methods integrating IRT with biometric measurement techniques and creating datasets for assessing individual conditions. This advancement supports evaluating psychological health in children and adolescents.